2011
DOI: 10.1681/asn.2010040355
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk for Dialysis or Death in IgA Nephropathy

Abstract: For the individual patient with primary IgA nephropathy (IgAN), it remains a challenge to predict long-term outcomes for patients receiving standard treatment. We studied a prospective cohort of 332 patients with biopsy-proven IgAN patients followed over an average of 13 years. We calculated an absolute renal risk (ARR) of dialysis or death by counting the number of risk factors present at diagnosis: hypertension, proteinuria Ն1 g/d, and severe pathologic lesions (global optical score, Ն8). Overall, the ARR sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
236
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(250 citation statements)
references
References 40 publications
10
236
2
2
Order By: Relevance
“…However, the patients in the present study showed only 10% of ESRD, which reflected the relatively "low-risk" features of our cohort compared with other published cohorts. In fact, most of our patients had relatively low-grade proteinuria (,1 g/d) and low-risk pathologic features, and fewer had hypertension and advanced CKD stage than those in previous studies (6,8,17,37). Thus, one should take care in applying the risk scores developed in the present study to a traditionally high-risk population of patients with IgAN.…”
Section: Variables Scoresmentioning
confidence: 77%
See 3 more Smart Citations
“…However, the patients in the present study showed only 10% of ESRD, which reflected the relatively "low-risk" features of our cohort compared with other published cohorts. In fact, most of our patients had relatively low-grade proteinuria (,1 g/d) and low-risk pathologic features, and fewer had hypertension and advanced CKD stage than those in previous studies (6,8,17,37). Thus, one should take care in applying the risk scores developed in the present study to a traditionally high-risk population of patients with IgAN.…”
Section: Variables Scoresmentioning
confidence: 77%
“…We believe that this score will be useful for determining the initial therapeutic strategies of patients with IgAN. Several risk scores for developing ESRD in patients with IgAN have been reported previously (2,8,17). However, these studies had several limitations.…”
Section: Variables Scoresmentioning
confidence: 98%
See 2 more Smart Citations
“…Proteinuria is regarded as a risk factor for an unfavorable renal prognosis and the reduction of proteinuria is considered an important therapeutic goal in clinical practice (35). In addition to proteinuria, active renal lesions, such as cellular crescent formation, diffuse mesangial proliferation and interstitial inflammatory infiltration have been identified to result in a rapid rate of deterioration and lower kidney survival (6).…”
Section: Introductionmentioning
confidence: 99%